Synthesis method and application of low-addition-amount dispersing and bonding two-in-one polymer emulsion for negative electrode of lithium ion battery

The polyacrylate polymer emulsion (PAAR-) synthesized through block polymerization technology as the negative electrode binder of lithium-ion batteries solves the problems of high additive amount and complex process in the prior art, and achieves battery performance with lower internal resistance, better rate performance and higher peel strength.

CN119505061APending Publication Date: 2025-02-25HUIZHOU SAILIDA IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411904984.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode binder system has disadvantages in reducing the additive amount and simplifying the process flow, resulting in the performance not meeting market requirements.

Method used

By block polymerization, a long chain segment with dispersible properties and a spherical polymer segment with high adhesion are polymerized on the same polymer chain to form a polyacrylate polymer emulsion (PAAR-) as the negative electrode binder.

Benefits of technology

It is achieved to improve the conductivity, rate performance and electrode stripping strength of the battery while reducing the amount of polymer additives, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505061A_ABST
    Figure CN119505061A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode binders, in particular to a synthesis method and application of a lithium ion battery negative electrode low-addition-amount dispersing and bonding two-in-one polymer emulsion. The polymer emulsion is a polyacrylate polymer material, and a long chain segment with dispersity is dispersed into a long chain segment in a block polymerization mode to form the polymer emulsion with the low-addition-amount dispersing and bonding two-in-one polymer emulsion with the low-addition-amount dispersing and bonding two-in-one polymer emulsion with the low-addition-amount dispersing and bonding two-in-one. The spherical high-molecular segments with high adhesion are polymerized on the same high-molecular chain, and the formula comprises a main monomer, a functional monomer, an emulsifier, an initiator and process water. According to the invention, a long-chain segment with dispersibility and a spherical high-molecular segment with high adhesion are polymerized on the same high-molecular chain in a block polymerization manner. Therefore, the overall performance of PAAR-also has the dispersibility to the graphite as a main material of the negative electrode, and also has very strong adhesion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery negative electrode binders, in particular to a synthesis method of a low-addition dispersion and bonding two-in-one polymer emulsion for lithium ion battery negative electrodes and its application. Background Art

[0002] The common negative electrode binder system of lithium-ion batteries on the market is mainly CMC (carboxymethyl cellulose) + SBR (styrene-butadiene rubber). The dispersion and bonding functions of the negative electrode main material graphite are achieved through the dispersibility of CMC and the bonding and flexibility of SBR. The traditional formula addition ratio is CMC: SBR: SP (conductive agent): C (graphite) = 1.2: 1.8: 1.0: 96.0. As the technology of lithium-ion batteries matures and the market competition gradually intensifies, the performance requirements for them are increasingly moving towards high energy density, performance improvement and process optimization.

[0003] The mainstream of the existing negative electrode binder system is the CMC+SBR (1.2%: 1.8%) system, and a small number of them use the PAA (polyacrylic acid) system. However, the existing system has certain disadvantages in reducing the amount of additives added or reducing the process flow. The CMC+SBR system has been very mature after decades of research and development and market verification, but due to the low adhesion of CMC and the almost no dispersion performance of SBR, the two must be matched. Due to their complementary performance, any decrease in the amount of addition of the two will cause a decrease in the dispersion of the slurry or the peeling strength of the pole piece, thus failing to meet the market's performance requirements. Pure water-based PAA has better adhesion than CMC and better dispersibility than SBR, but the negative pole piece made of PAA alone is harder and more brittle. The disadvantage of process performance makes most application scenarios use some CMC+SBR for use, which makes the process flow more complicated and cannot balance between reduced addition and stable performance.

[0004] Therefore, in order to correct the above defects, we proposed a synthesis method and application of a low-addition dispersion bonding two-in-one polymer emulsion for lithium-ion battery negative electrode. Summary of the invention

[0005] The technical problem solved by the present invention is to propose a synthesis method and application of a low-addition dispersion and bonding two-in-one polymer emulsion for lithium-ion battery negative electrode, and to develop a dispersion and bonding two-in-one polymer emulsion as a lithium-ion battery negative electrode binder, the polymer is a polyacrylate polymer, hereinafter collectively referred to as PAAR-. The present invention aims at the disadvantages of the above prior art, while satisfying the requirement of reducing the addition amount of lithium-ion battery additives, so that the manufactured battery has the advantages of lower internal resistance, better rate performance and the like.

[0006] To achieve the above objectives, the first objective of the present invention is to provide a low-addition dispersing and bonding two-in-one polymer emulsion for lithium-ion battery negative electrode, wherein the polymer emulsion is a polyacrylate polymer material, and a long chain segment with dispersibility and a spherical polymer segment with high adhesion are polymerized on the same polymer chain by block polymerization, and the formula includes a main monomer, a functional monomer, an emulsifier, an initiator, and process water; The main monomers are styrene and acrylate; The functional monomer is one of butyl acrylate, isooctyl acrylate, methacrylic acid, methyl methacrylate, vinyl acetate, acrylamide, hydroxyethyl acrylate, and hydroxypropyl acrylate; The emulsifier is one of alkyl polyoxyethylene ether, alkyl sulfonate, alkyl ether sulfate, and alkyl ether succinic platinum sulfonate; The initiator is persulfate.

[0007] The second object of the present invention is to provide a method for synthesizing the low-addition dispersion and bonding two-in-one polymer emulsion for lithium ion battery negative electrode as described above, which comprises the following steps: S1. Pump the main monomer, functional monomer material, emulsifier and process water required for pre-emulsification into the pre-emulsification kettle, start stirring for pre-emulsification, and obtain a pre-emulsion; S2, adding initiator and process water into the initiator kettle, stirring evenly to obtain an initiator solution; S3, putting the primer emulsifier and process water into the polymerization kettle, heating and stirring to mix; S4, adding the primer pre-emulsion into the polymerization kettle, continuing heating, and then adding the primer initiator to carry out the primer reaction. After the primer reaction is completed, the pre-emulsion in step S2 is added dropwise to carry out the synthesis reaction for 4 to 6 hours. As the reaction proceeds, cooling water is added to the jacket of the polymerization kettle to control the reaction temperature; S5. After the polymerization reaction is completed, the temperature in the kettle is reduced to below 50°C after a heat preservation process and cooling, and a post-treatment agent is added for post-treatment adjustment.

[0008] Furthermore, in step S3, the temperature is heated to 80-86°C.

[0009] Furthermore, in step S4, when the primer initiator is added, the temperature of the polymerization kettle rises to 78-84°C, and the pre-emulsion in step S2 is started to be added dropwise to carry out the synthesis reaction. The temperature is controlled at 80-86°C, and cooling water is added to the jacket of the polymerization kettle to control the reaction temperature to 80-86°C.

[0010] The third object of the present invention is to provide a polymer emulsion synthesized by the above-mentioned method for synthesizing the low-addition dispersion and bonding two-in-one polymer emulsion for lithium-ion battery negative electrode for application in lithium-ion battery manufacturing.

[0011] Compared with the prior art, the beneficial effect of the present invention is that long chain segments with dispersibility and spherical polymer segments with high adhesion are polymerized on the same polymer chain by block polymerization. The overall performance of PAAR- has both dispersibility to the negative electrode main material graphite and strong adhesion. In addition, the polymer has the properties of some polymer electrolytes. By replacing the hydrogen ions in the carboxylate groups on the polymer chain with lithium ions, it contains a certain amount of lithium carboxylate, which improves the ion conductivity: 1. While reducing the amount of polymer additives added, the amount of conductive agent SP added is also reduced from the traditional 1.0% to 0.6%, achieving lower battery internal resistance; 2. The rate performance of the manufactured battery is significantly improved; 3. When the total amount of dispersed binder is reduced, the peel strength is increased by 20-30%; 4. The battery's 1C cycle performance at room temperature has been improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a schematic diagram of the reaction equation in the present invention; Figure 2 It is a process flow chart of the present invention; Figure 3 This is a comparative experimental parameter table in the present invention; Figure 4 A schematic diagram showing the comparison between the initial electrical performance of the battery cell of the present invention and the initial electrical performance of the battery cell in the comparative example; Figure 5 It is a schematic diagram of the peeling force effect of the electrode in the present invention; Figure 6 It is a rate discharge comparison curve diagram in the present invention; Figure 7 It is a schematic diagram for comparing the normal temperature 1C cycle in the present invention. DETAILED DESCRIPTION

[0013] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] The present invention provides a technical solution: See also Figure 1-3, a synthesis method and application of a low-addition dispersion bonding two-in-one polymer emulsion for lithium-ion battery negative electrode.

[0015] Emulsion polymerization adhesive is an adhesive made by polymerization reaction of suitable monomers with suitable emulsifiers and initiators in water under certain conditions by emulsion polymerization. The present invention is a polyacrylate polymer material, the main monomers are styrene and acrylate, and suitable functional monomers are selected, including but not limited to butyl acrylate, isooctyl acrylate, methacrylic acid, methyl methacrylate, vinyl acetate, acrylamide, hydroxyethyl acrylate, hydroxypropyl acrylate, etc., suitable emulsifiers include but are not limited to alkyl polyoxyethylene ethers, alkyl sulfonates, alkyl ether sulfates, alkyl ether succinic platinum sulfonates, etc., and suitable initiators include but are not limited to persulfates.

[0016] Through block polymerization, the long chain segments with dispersibility and the spherical polymer segments with high adhesion are polymerized on the same polymer chain. This makes the overall performance of PAAR- have both dispersibility to the negative electrode main material graphite and strong adhesion. In addition, this polymer has the properties of some polymer electrolytes. By replacing the hydrogen ions in the carboxylate groups on the polymer chain with lithium ions, it contains a certain amount of lithium carboxylate, which improves the ion conductivity. The reaction equation is as follows: Figure 1 shown.

[0017] The process is a semi-continuous process, which includes material preparation, heating and dissolving, synthesis reaction, cooling, adjustment, testing, filtration, packaging and other processes. The production process takes about 8 hours. Figure 2 shown.

[0018] The specific process steps are as follows: A. Material preparation: Liquid raw materials are weighed and fed automatically, and solid raw materials are fed manually. It includes three parts: first, the monomer material, emulsifier and process water required for pre-emulsification are pumped into the pre-emulsification kettle, and stirring is started for pre-emulsification to obtain pre-emulsion; second, the initiator and process water are added to the initiator kettle, stirred evenly, and the initiator solution is obtained; third, the primer emulsifier and process water are added to the polymerization kettle, and stirred and mixed evenly.

[0019] B. Heating: Heat the polymerization kettle to 80-86°C and stir to mix.

[0020] C. Synthesis reaction: Add the pre-emulsion from the pre-emulsion kettle to the polymerization kettle, continue heating, and add the primer initiator when the temperature rises to 78-84°C to carry out the primer reaction. After the primer reaction is completed, start to drop the pre-emulsion to carry out the synthesis reaction. The temperature is controlled at 80-86°C, and the time is about 4-6 hours. As the reaction proceeds, cooling water will be added to the jacket of the reactor to control the reaction temperature at 80-86°C.

[0021] D. Cooling: After the polymerization reaction is completed, the temperature in the kettle is reduced to below 50°C after the heat preservation process and cooling, and the post-treatment agent is added for post-treatment adjustment.

[0022] E. Packaging and discharging: After adjustment and inspection, the materials are filtered, packaged and discharged.

[0023] Through repeated experimental verification, compared with the binder system of CMC+SBR (1.2%:1.8%), the total amount of dispersed binder PAAR- was reduced to 2.2%, achieving the following results: 1. While reducing the amount of polymer additives added, the amount of conductive agent SP added is also reduced from the traditional 1.0% to 0.6%, achieving lower battery internal resistance; 2. The rate performance of the manufactured battery is significantly improved; 3. When the total amount of dispersed binder is reduced, the peel strength is increased by 20-30%; 4. The battery's 1C cycle performance at room temperature has been improved.

[0024] The following is the experimental results data: like Figure 3 As shown, the experimental parameters are compared: When all other conditions for making the battery, including the formula of the positive electrode material, were the same, two control groups were selected and used different SBRs (104A and 451B) respectively, and compared with the experimental group using only PAAR- (codenamed SJ312).

[0025] The initial electrical performance of the battery cell is that the discharge capacity is increased by about 0.5-1%, and the internal resistance is reduced by 3-5%. By reducing the amount of binder added and increasing the amount of graphite main material by 1%, the discharge capacity is increased. Since the polymer of the present invention has the properties of a part of the polymer electrolyte, the ion conductivity of the battery is improved, thereby reducing the internal resistance, such as Figure 4 shown.

[0026] Since the present invention is a polymer with dispersed bonding, while the total amount of the overall dispersed adhesive system is reduced, the molecular weight of the high bonding force is actually increased, so that the electrode peeling force is increased by more than 20%. Figure 5 shown.

[0027] Due to the reduction of internal resistance, the rate performance is significantly improved by 4-5%, such as Figure 6 shown.

[0028] High adhesion also improves the cycle performance. During long-term use, the battery will not suffer performance degradation due to the shedding of the main material. Figure 7 shown.

[0029] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low-addition dispersion and bonding two-in-one polymer emulsion for lithium-ion battery negative electrode, characterized in that: The polymer emulsion is a polyacrylate polymer material, which is polymerized on the same polymer chain by block polymerization of long-chain segments with dispersibility and spherical polymer segments with high adhesion. The formula includes main monomers, functional monomers, emulsifiers, initiators, and process water. The main monomers are styrene and acrylate; The functional monomer is one of butyl acrylate, isooctyl acrylate, methacrylic acid, methyl methacrylate, vinyl acetate, acrylamide, hydroxyethyl acrylate, and hydroxypropyl acrylate; The emulsifier is one of alkyl polyoxyethylene ether, alkyl sulfonate, alkyl ether sulfate, and alkyl ether succinic platinum sulfonate; The initiator is persulfate.

2. A method for synthesizing the low-addition dispersion and bonding two-in-one polymer emulsion for lithium-ion battery negative electrode according to claim 1, characterized in that: The steps include: S1. Pump the main monomer, functional monomer material, emulsifier and process water required for pre-emulsification into the pre-emulsification kettle, start stirring for pre-emulsification, and obtain a pre-emulsion; S2, adding initiator and process water into the initiator kettle, stirring evenly to obtain an initiator solution; S3, putting the primer emulsifier and process water into the polymerization kettle, heating and stirring to mix; S4, adding the primer pre-emulsion into the polymerization kettle, continuing heating, and then adding the primer initiator to carry out the primer reaction. After the primer reaction is completed, the pre-emulsion in step S2 is added dropwise to carry out the synthesis reaction for 4 to 6 hours. As the reaction proceeds, cooling water is added to the jacket of the polymerization kettle to control the reaction temperature; S5. After the polymerization reaction is completed, the temperature in the kettle is reduced to below 50°C after a heat preservation process and cooling, and a post-treatment agent is added for post-treatment adjustment.

3. The method for synthesizing the low-addition dispersion-bonding two-in-one polymer emulsion for lithium-ion battery negative electrode according to claim 2, characterized in that: In the step S3, the temperature is raised to 80-86°C.

4. The method for synthesizing the low-addition dispersion-bonding two-in-one polymer emulsion for lithium-ion battery negative electrode according to claim 2, characterized in that: In step S4, when the primer initiator is added, the temperature of the polymerization kettle rises to 78-84°C, and the pre-emulsion in step S2 is added dropwise to carry out the synthesis reaction. The temperature is controlled at 80-86°C, and cooling water is added to the jacket of the polymerization kettle to control the reaction temperature to 80-86°C.

5. A polymer emulsion synthesized by the method for synthesizing a low-addition dispersion-bonding two-in-one polymer emulsion for a lithium-ion battery negative electrode according to any one of claims 2 to 4 is used in the manufacture of lithium-ion batteries.